Effects of Curcumin on Nitrosyl-Iron Complex – Mediated DNA Cleavage and Cytotoxicity - Shiau, Rong-Jen; Wu, Jheng-Yu; Chiou, Show-Jen; Wen, Yu-Der (Planta Medica, 2012)
Combination therapy aims to improve the pharmaceutical efficacy of different drugs, thus lowering the dosages used and reducing the side effects. However, interactions between individual drugs may also occur and lead to uncertain consequences. This study demonstrated that curcumin, a natural phenolic compound found in the rhizomes of turmeric, could either inhibit or enhance DNA cleavage caused by the synthetic nitrosyl-iron complex NC10 ([Fe2(C2H5OS)2(NO)4]). Without UV irradiation, higher concentrations of curcumin protected DNA from being cleaved by NC10. Conversely, in the presence of lower concentrations of curcumin (< 5 µM), cleaved DNA increased by raising curcumin concentrations. After UV irradiation, the DNA protective effect of curcumin decreased while the enhancing DNA cleavage effect of curcumin remained. UV/visible spectroscopy analysis showed that curcumin is associated with the iron of NC10, suggesting the formation of curcumin-Fe complexes. Furthermore, a cytotoxicity assay revealed that cotreatment of NC10 and curcumin had synergetic effects on the growth inhibition of mouse melanoma B16-F10 cells. To our knowledge, this is the first study of the cotreatment of curcumin with inorganic compounds that showed synergistic cytotoxicity.
Keywords: curcumin; Curcuma longa; Zingiberaceae; cytotoxicity; DNA cleavage; metal-nitrosyl complexes